Desmoplastic Ameloblastoma: A Report of Two Cases - Konchanthes, Sasithorn; Chamusri, Nutchapon (Chiang Mai Dental Journal, 2019)
Among the ameloblastomas, the desmoplastic variation is a rare variant that accounts for approximately 4–13 %. The desmoplastic ameloblastoma displays significant differences in anatomical sites, radiographic features and histologic appearances from the other ameloblastoma subtypes. We here present two patients with desmoplastic ameloblastomas in the maxilla and the mandible. Clinically, both patients presented with painless swelling of the jaw bone. An ill-defined, mixed radiolucent-radiopaque appearance was evident on panoramic radiographs. The definitive diagnosis of desmoplastic ameloblastomas were achieved by incisional biopsies. Subsequently, partial resection of the maxilla or the mandible were performed. The patients are on routine follow-up. No sign of recurrence was observed.